Pedagogy, Symbolic Control, and Identity - Bernstein, Basil (Rowman & Littlefield Publishers, 2000)
This book, the fifth in the series developing Bernstein’s code theory, presents a lucid account of the most recent developments of this code theory and, importantly, shows the close relation between this development and the empirical research to which the theory has given rise. Pedagogy, Symbolic Control and Identity addresses the central issue of Bernstein’s research project: are there any general principles underlying the transformation of knowledge into pedagogic communication? In Bernstein’s view, we have studied only pedagogic messages and their institutional and ideological base. We have not studied the nature of the relay which makes messages possible. The discussion of this research forms part II of this book, where Bernstein makes explicit the methodology of the research and, in particular, the crucial significance of languages of description. This new edition of Bernstein's classic book is updated with three new chapters: on discourse, on official knowledge and identities, and a wide ranging interview with Joseph Solomon. The new edition, published as Volume Five in his Class, Codes, and Control Series, builds on the continuing tradition of Bernstein's highly influential work on class, education, language, and society.